Synergy of Artificial Intelligence and Prophetic Pedagogy in Enhancing Students’ Critical Thinking - Maulana Teguh Perdana; Maulana Paramaditya Ananta (Institut Bahri Asyiq Galis Bangkalan, 2026)
The advancement of artificial intelligence in higher education has created both opportunities and challenges in developing students’ critical thinking. While this technology has enhanced learning efficiency and accessibility, its unregulated use has risked weakening reflective and analytical capacities. Therefore, a pedagogical approach that integrates technological and value-based dimensions has become essential. This study aimed to analyze the synergy between artificial intelligence and prophetic pedagogy in enhancing students’ critical thinking. A descriptive qualitative approach with a meta-analysis method was employed, examining literature published between 2016 and 2025 from reputable digital databases. Data were collected through systematic digital documentation, while content and thematic analyses were applied for data interpretation. The findings indicated that artificial intelligence functioned effectively as an adaptive learning tool but required a value-based framework to optimize critical thinking development. The integration of prophetic pedagogy strengthened students’ reflective, ethical, and analytical dimensions. This study contributed to the development of an integrative paradigm that connects technology and values as a foundation for holistic and meaningful learning.